Proteins Obtained from Dunaliella Salina Algae and Their Application in Gelation Processes and Metal Binding Compared to Legume Proteins - Szewczyk, Rafał (Białka pozyskiwane z alg Dunaliella salina i ich zastosowanie w procesach żelowania i wiązaniu metali na tle białka z roślin strączkowych, 2025)
Aim: Identification of research gap regarding the functional properties of microalgal proteins, specifically Dunaliella salina. The analysis aimed to determine whether these microalgal proteins exhibit similar properties to proteins from the following legumes: soybeans, lentils, chickpeas, and peas. The focus was on two key functional characteristics, i.e. gelation properties and metal binding properties. Methodology: The analysis was based on a review of the scientific literature using the Mendeley database. The search included English-language keywords related to legume proteins and Dunaliella salina, particularly their functional properties. The selected publications were divided into two main thematic groups, namely protein composition and fractions, and their gelling and metal-binding capacity. Additionally, a quantitative analysis of the obtained results was performed to assess the research intensity for each species. Results: A significant disparity in data availability was demonstrated between legumes and D. salina. While proteins from soybeans, peas, lentils, and chickpeas have been thoroughly characterised in terms of their function, the literature on Dunaliella salina is limited to general information on protein content and some studies on bioactive peptides. However, studies on the ability of these proteins to form gels and bind heavy metals are lacking, hence the results indicate a knowledge gap in this area. Implications and recommendations: The identified research gap highlights the need for in-depth experimental studies on the functionality of D. salina proteins. It is recommended to evaluate their gelling properties and metal-binding capacity, and the findings of such studies could have applications in the food industry. The potential of microalgae as an alternative protein source warrants further research. Originality/value: This work contrasts the functional properties of legume proteins with the limited knowledge of Dunaliella salina proteins. It identifies a research gap in the area of microalgae as a potential source of functional proteins. It provides a basis for planning further studies on D. salina proteins in the context of their suitability for food applications.
Nauki Inżynierskie i Technologie = Engineering Sciences and Technologies, 2025, Nr 41, s. 33-41